Search for Knowledge and Recognition : Traditional Qur'anic Students in Kano, Nigeria - Hannah Hoechner (IFRA-Nigeria, 2013)
Hannah Hoechner investigates an educational practice that is widespread in Muslim West Africa. (3z(BTraditional(3y (BQur$1 (Banic schools, whose students live with their teacher and earn their own livelihood (often through begging), have become the subject of much public concern and anxiety. Hannah Hoechner explores the experience of such Qur$1 (Banic students (pl. almajirai; sg. almajiri) in Kano State in northern Nigeria. The almajirai have attracted attention in the context of increased attempts to universalise primary education and of growing concerns about child welfare. They have also been rightly or wrongly associated with Islamic radicalisation, militancy, and the periodic riots that have blighted many northern Nigerian cities. The current spate of Boko Haram violence in northern Nigeria has carried such modes of thinking to the extreme. The Qur$1 (Banic schools are described as a (3z(Bticking time bomb(3y (Band a (3z(Bthreat(3y (Bto national security. Despite the concern and controversy sparked by the almajirai, there is a dearth of research engaging directly and in depth with the constituencies of the (3z(Btraditional(3y (BQur$1 (Banic schooling system. That the existing literature does not contribute to a better understanding of the system is a particularly severe shortcoming, given the enthusiasm with which speculative narratives are constructed in some sections of the media. Such narratives craft their own realities, as people act upon their stereotypes. Hannah Hoechner$1 (Bs research aims to fill the gap in knowledge about almajirai. She explores the processes through which children become almajirai and what they learn while they are living as almajirai. She also engages with the (overwhelmingly negative) representations of the system and asks how young people living as almajirai position themselves with respect to such representations.s
English
Keywords: Islam; Nigerian muslims; Qur$1 (Banic schoolss; religion